Peningkatan Kemampuan Motorik Kasar Anak Usia 4-5 Tahun Melalui Metode Senam Fantasi - Fadlun Maulin; Lizza Suzanti; Rr. Deni Widjayatri (Universitas Pendidikan Indonesia Kampus Serang, 2019)
This research was conducted based on findings in the field regarding the gross motor abilities of children in A Muharram group that have not been optimal. It is necessary to find the appropoate method to develope their gross motoric skills. Gross motoric skill development is very important for early childhood because it can affect their future. One of various ways to develop their motoric skills is through fantasy gymnastic method. This study aims to improve the gross motor skills of children aged 4-5 years through fantasy gymnastic methods. The method used is a classroom action research method. The subjects of this study were nine children aged 4-5 years of Muharram group consisting of five boys and four girls in early childhood education of Bina Bangsa Islamic School of Serang. The data collection techniques are conducted through interviews and observations using designed form of interview and observation sheets. The data analysis techniques used interactive model by Miles and Huberman. The percentage result obtained from the pre cycle was 34,70% (bad), then increased in cycle I to be 62,80% (good) and then in cycle II to be 87,50% (very good). It can be concluded that the fantasy gymnastic method can improve gross motor skills of children aged 4-5 years of early childhood education of Bina Bangsa Islamic School of Serang. The result propose the use of gymnastic and other method to be used in the other aspects of motoric development.